2010
DOI: 10.1007/s10549-010-1175-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of ethnic variations in TNF-α and TNF-β polymorphisms and risk of breast cancer in India

Abstract: TNF-α and -β, the multi-functional pro-inflammatory cytokines, are known to play important roles in both tumor progression and destruction based on their concentrations. Growth factors and various stimuli such as cytokines regulate proliferation of the breast epithelial cells. Therefore, the polymorphisms in the genes encoding these signaling molecules could affect the risk of breast cancer. We have investigated selected genetic polymorphisms in TNF-α promoter (rs1800629, -308 G>A and rs361525, -238 G>A) and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 34 publications
0
26
1
Order By: Relevance
“…In our population, the frequency of this polymorphism was 14% in BC patients and 1% in controls and was identified as a risk factor. Other studies have observed the association between the -308G>A polymorphism and BC (Li et al, 2008;Pooja et al, 2011;Shen et al, 2011).…”
Section: Discussionmentioning
confidence: 88%
“…In our population, the frequency of this polymorphism was 14% in BC patients and 1% in controls and was identified as a risk factor. Other studies have observed the association between the -308G>A polymorphism and BC (Li et al, 2008;Pooja et al, 2011;Shen et al, 2011).…”
Section: Discussionmentioning
confidence: 88%
“…Accordingly, it is rational to speculate that TNF-α -308G>A and -238G>A polymorphisms may have an impact on the development of some types of cancers. In recent years, numerous casecontrol studies have been conducted to investigate the associations of TNF-α -308G>A and -238G>A promoter region polymorphisms with cancer risk, suggesting that these polymorphisms may be associated with cancer susceptibility, such as breast cancer, lung cancer, nasopharyngeal cancer and cervical cancer (Deshpande et al, 2005;Shih et al, 2006;Pooja et al, 2011;Sousa et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…16,19 Similarly, in two North India studies, polymorphism was significantly associated with breast cancer susceptibility with OR of 1.43 and 2.38. 20,21 Our study, comprising more of south India women may show ethnic variation. The lack of significant association of rs 909253 SNP is consistent with the previous studies from the US and Iran.…”
Section: Discussionmentioning
confidence: 93%